PELAYANAN LANGSUNG JADI KABUPATEN JOMBANG - Zulfani, Melia Aninda (Jurnal Transformative, 2017)
Governance today is no longer solely the responsibility of government, but of all the actors in a country. Why this is so, the role of government is certainly still needs related to the provision of public services. The problems that exist in Jombang is difficult licensing services, too complicated, time-consuming, expensive cost plus the community was thinking radically. They still do not understand the meaning of taking care of a license for what and what's in it for them, especially people in remote villages that are unreachable information. Given this reality, Jombang Jombang Regent, H. Suyanto, initiates in licensing by making services with procedure "Pick up Ball". With reference to the Minister Regulation No.24 of 2006 on One Stop Services and decree No. 11 Year 2008 on Main Duties and Functions of Licensing Service Agency. The mechanism of this program is to go to 22 sub-districts in Jombang to give services to the community as well as socialization. This activity is carried out since the second week until the next 22 days starting one day be filled in one sub-district. Making this program has great benefits for society because it does not need to take a long time also does not charge in the permits, in addition to the public confidence has also been quite high.